1995
DOI: 10.1159/000106917
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Alpha<sub>1</sub>-Antichymotrypsin Serum Levels in a Subset of Nondemented First-Degree Relatives of Alzheimer's Disease Patients

Abstract: A portion of Alzheimer''s disease (AD) patients have elevated serum levels of the acute phase reactant α1-antichymotrypsin (A1ACT) compared to age-matched controls. We measured serum levels of A1ACT in AD patients, age-matched controls, Down''s Syndrome patients, and nondemented first-degree relatives of AD patients. Significantly elevated levels of A1ACT were found in both AD patients and first-degree-relatives. In AD patients, serum A1ACT concentrations decreased with increasing severity of cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
2
13
1
Order By: Relevance
“…These findings excluded the presence of a systemic inflammation in AD [21]. Elevated levels of serum ACT have also been reported in a subset of first-degree relatives of AD patients [23], and it has been suggested that serological ACT may represent a useful biological marker to monitor the disease [23]. However, other studies could not confirm the above findings and reported normal levels of ACT from peripheral blood of AD patients [24][25][26].…”
Section: Introductionmentioning
confidence: 93%
“…These findings excluded the presence of a systemic inflammation in AD [21]. Elevated levels of serum ACT have also been reported in a subset of first-degree relatives of AD patients [23], and it has been suggested that serological ACT may represent a useful biological marker to monitor the disease [23]. However, other studies could not confirm the above findings and reported normal levels of ACT from peripheral blood of AD patients [24][25][26].…”
Section: Introductionmentioning
confidence: 93%
“…Elevated ACT concentrations have been widely but not universally reported in AD patients [22,23]. Recently, Gabriel et al [24] extended this finding and demonstrated the association between elevated ACT and cognitive impairment in a medically stable elderly population.…”
Section: Discussionmentioning
confidence: 97%
“…Elevated scrum levels of ACT in patients with AD have been reported by some laboratories [5][6][7][8], but not others [26,27], Increased deposition of ACT in the brain in AD may be part of a 'cerebral acute phase response' contributing to neuronal loss [28,29], If serum levels of ACT reflect inflammatory activity in the brain, they may provide an accessible measure to guide anti-inflammatory therapy. But the validity of this idea will only be deter mined when the results of a full-scale therapeutic trial become available.…”
Section: Discussionmentioning
confidence: 99%
“…karger, ch serve as a peripheral marker of cerebral inflammatory activity [5][6][7][8]. All of the tissue-bound products of the clas sical pathway of complement activation arc found in the area of senile plaques, including the membrane attack complex which may lvsc neuronal membranes [3,[9][10][11].…”
Section: Karg Ermentioning
confidence: 99%
See 1 more Smart Citation